(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2012)
Management Representations Letter plays a significant role as an evidence to get conclusions the Auditor is looking for. These conclusions could show the professional opinion of auditor over the fairness and integrity of financial statements for many issues and numbers that management claims, Hereby, the research aims at highlighting the importance of Management Representations Letter and the way of using as an evidence with expressing its meaning and means of application in addition to identify the Responsibility of Auditor on that Letter, This research discusses also the effect of Management Representations Letter on the credibility of financial statement and enhancing the credibility of the submitted reports, From other side, in the theoretical and practical sides, research presents a set of commendations among of which are the auditor the person who takes directly the responsibility of detailed statement in the Management Representations Letter and the responsibility of presenting unrestricted opinion or other wise the auditor doesn’t get the management representations letter if he would preface to apologize, Accordingly, he research shows a set of recommendations, among of which are the council of control and accounting standards of Iraq should exert its efforts to issue Iraqi audit evidence based on IA S" amended" No.(580), works in line with the main national auditing environment